Antibody persistency and trend post-SARS-CoV-2 infection at eight months - Dehgani-Mobaraki, P.; Kamber Zaidi, A.; Porreca, A.; Floridi, A.; Floridi, E.; Monti, M.; Dehgani-Mobaraki, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. A large amount of recent research has focused on the nature of immunity elicited by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, particularly its robustness and the duration of protection it offers. As a vaccine’s efficacy relies on its ability to induce a protective immune response, these questions remain particularly pertinent. An improved understanding of the immunity offered by the antibodies developed against SARS-CoV-2 in recovered patients is critical for the development of diagnostic tests and vaccines. Methods. Our study aimed at the longitudinal analysis of antibody presence, persistence and its trend over eight months in a group of 30 COVID-19 recovered patients who tested positive by real-time quantitative PCR for SARS-CoV-2 in the period 1-30 March 2020. The subjects were divided into two groups based on disease severity: mild (n=17 subjects) and moderately-severe (n=13 subjects). The MAGLUMI 2019-nCoV lgM/lgG chemiluminescent analytical system (CLIA) assay was used to analyze these antibody titres. Results. IgG antibody persistency was demonstrated in 76.7 % of the subjects (23 out of 30) at eight months post-infection. For the moderately-severe group, the titre trends for both IgM and IgG changed in a statistically significant way throughout the time period with IgM below and IgG above the set cut-off.Conclusions. The results of this study highlight an important point in terms of the association between humoral immune response and disease severity. Patients who have experienced a relatively severe infection might develop a stronger immune response that could persist for a longer period.